Art-Paper. - Dominikanerkerk, Maastricht; Gemeentemuseum, Arnhem; Leopold-Hoesch-Museum, Düren; Provinciaal Museum, Hasselt; Stedelijk Museum "Het Prinsenhof", Delft (Maastricht : Jan Van Eyck Akademie, 1987)
Buisman, Sjoerd ; Capone, Vito ; Denmark ; Dirnaichner, Helmut ; Duchateau, Hugo ; Fisher, Joël ; Giezen, Krijn ; Lohaus, Bernd ; Mach, David ; Oppenheim, Meret ; Peeters, Sef ; Pietsch, Heinz-Dieter ; Pupkiewicz, Thomas ; Weber, Thérèse ; Van den Dool, Engelien
Art-Paper, Dominikanerkerk, Maastricht ; Gemeentemuseum, Arnhem ; Leopold Hoesch Museum, Düren ; Provinciaal Museum, Hasselt ; Stedelijk Museum 'Het Prinsenhof', Delft, 1987
boek